Financial management in construction contracting - Ross, Andrew, 1960-; Williams, Peter (Chichester, West Sussex ; Ames, Iowa : Wiley-Blackwell, 2013)
"This textbook provides a general introduction to costing and budgeting for construction but in particular it covers CVRs. There is a wide range of approaches to preparing these reports and, without being over-prescriptive, the authors provide a useful framework for students by giving an outline of the key requirements, together with an evaluation of the alternatives"--
Machine generated contents note: Chapter 1 Introduction and Context. Chapter 2 Principles of Management Accounting. Chapter 3 Costs - Information and Reporting Chapter 4 Value. Chapter 5 Cost And Value Reconciliation. Chapter 6 'Softer Issues'. Chapter 7 CVR - Review of Current Practice. Chapter 8 Future Issues and New Direction.
engineering bookfair2015
Includes bibliographical references and index.
Keywords: Construction industry -- Accounting; Construction industry -- Finance; TECHNOLOGY & ENGINEERING / Civil / General